Biodiesel's Characteristics Preparation from Palm Oil - S, Tilani Hamid.; Yusuf, Rachman (UI Scholars Hub, 2002)
Biodiesel’s characteristics preparation from palm oil. Using vegetable oils directly as an alternative diesel fuel has presented engine problems. The problems have been attributed to high viscosity of vegetable oil that causes the poor atomization of fuel in the injector system and pruduces uncomplete combustion. Therefore, it is necessary to convert the vegetable oil into ester (metil ester) by tranesterification process to decrease its viscosity. In this research has made biodiesel by reaction of palm oil and methanol using lye (NaOH) as catalyst with operation conditions: constant temperature at 60 oC in atmosferic pressure, palm oil : methanol volume ratio = 5 : 1, amount of NaOH used as catalyst = 3.5 gr, 4.5 gr, 5 gr and 5.5 gr and it takes about one hour time reaction. The ester (metil ester) produced are separated from glycerin and washed until it takes normal pH (6-7) where more amount of catalyst used will decrease the ester (biodiesel) produced. The results show that biodiesels’ properties made by using 3.5 (M3.5) gr, 4.5 gr (M4.5) and 5 (M5.0) gr catalyst close to industrial diesel oil and the other (M5.5) closes to automotive diesel oil, while blending diesel oil with 20 % biodiesel (B20) is able to improve the diesel engine performances.